AN ECOLOGICAL LITERACY ON CHILDREN’S ENVIRONMENTAL LITERATURE IN ANNA SEWELL’S BLACK BEAUTY - GADIS INDITA DWI NASTITI, 121411231057 (2018)
Animal plays an important role in human’s life. Yet, animal is often mistreated by human. The issue of human mistreating animal does exist in our society. People tend not to think about the condition of animal carefully. Therefore, this issue should be taken more seriously in order to reduce the activity of human’s cruel deeds towards animal. This study examines the issue of ecological literacy in a novel entitled Black Beauty by Anna Sewell (2011). The focus of this study is on the portrayal and the relationship between human and nature. This study aims to analyze the portrayal of human and nature, animal exploitation, animal rights, and ecological literacy. This study uses qualitative approach and ecological literacy theory by David W. Orr. From all the findings, the writer argues that in the framework of ecological literacy, the novel gives the reader Understanding that animals do have feelings as humans. Thus, the position between animal and human is equal. In addition, literary works about nature or environment have an essential role in making people realize that human should build harmony with other living creatures.